The endosperm cavity of wheat grains contains a highly hydrated gel of arabinoxylan. (May 2021) - Chateigner-Boutin, Anne-Laure; Alvarado, Camille; Devaux, Marie-Françoise; Durand, Sylvie; Foucat, Loïc; Geairon, Audrey; Grélard, Florent; Jamme, Frédéric; Rogniaux, Hélène; Saulnier, Luc; Guillon, Fabienne
Highlights: The wheat grain central endosperm cavity is filled with a gel-like structure. The gel-like structure autofluoresces under UV excitation. It contains fluorescent, water-absorbing and gel-forming feruloylated arabinoxylans. High and stable cavity water content suggests a role in regulating grain hydration. Abstract: Cereal grains provide a substantial part of the calories for humans and animals. The main quality determinants of grains are polysaccharides (mainly starch but also dietary fibers such as arabinoxylans, mixed-linkage glucans) and proteins synthesized and accumulated during grain development in a specialized storage tissue: the endosperm. In this study, the composition of a structure localized at the interface of the vascular tissues of the maternal plant and the seed endosperm was investigated. This structure is contained in the endosperm cavity where water and nutrients are transferred to support grain filling. While studying the wheat grain development, the cavity content was found to autofluoresce under UV light excitation. Combining multispectral analysis, Fourier-Transform infrared spectroscopy, immunolabeling and laser-dissection coupled with wet chemistry, we identified in the cavity arabinoxylans and hydroxycinnamic acids. The cavity content forms a "gel" in the developing grain, which persists in dry mature grain and during subsequent imbibition. Microscopic magnetic resonance imaging revealed that the gel is highly hydrated. Our results suggest that arabinoxylans are synthesized by the nucellar epidermis, released in the cavity where they form a highly hydrated gel which might contribute to regulate grain hydration.